3 Tesla magnetic resonance imaging in patients with cardiac implantable electronic devices: a single centre experience. Issue 2 (23rd November 2022) - Fluschnik, Nina; Tahir, Enver; Erley, Jennifer; Müllerleile, Kai; Metzner, Andreas; Wenzel, Jan-Per; Guerreiro, Helena; Adam, Gerhard; Blankenberg, Stefan; Kirchhof, Paulus; Tönnis, Tobias; Nikorowitsch, Julius
Abstract: Aims: Three Tesla (T) magnetic resonance imaging (MRI) provides critical imaging information for many conditions. Owing to potential interactions of the magnetic field, it is largely withheld from patients with cardiac implantable electronic devices (CIEDs). Therefore, we assessed the safety of 3T MRI in patients with '3T MRI-conditional' and 'non-3T MRI-conditional' CIEDs. Methods and results: We performed a retrospective single-centre analysis of clinically indicated 3T MRI examinations in patients with conventional pacemakers, cardiac resynchronization devices, and implanted defibrillators from April 2020 to May 2022. All CIEDs were interrogated and programmed before and after scanning. Adverse events included all-cause death, arrhythmias, loss of capture, inappropriate anti-tachycardia therapies, electrical reset, and lead or generator failure during or shortly after MRI. Changes in signal amplitude and lead impedance were systematically assessed. Statistics included median and interquartile range. A total of 132 MRI examinations were performed on a 3T scanner in 97 patients. Thirty-five examinations were performed in patients with 'non-3T MRI-conditional' CIEDs. Twenty-six scans were performed in pacemaker-dependent patients. No adverse events occurred during or shortly after MRI. P -wave or R-wave reductions ≥ 50 and ≥ 25%, respectively, were noted after three (2.3%) scans, all in patients with '3T MRI-conditional' CIEDs. Pacing and shock impedance changed by ± 30% in one case (0.7%). Battery voltage and stimulation thresholds did not relevantly change after MRI. Conclusion: Pending verification in independent series, our data suggest that clinically indicated MRI scans at 3T field strength should not be withheld from patients with cardiac pacemakers or defibrillators. Graphical Abstract: Graphical Abstract Abbreviations: CIEDs, cardiac implantable electronic devices; MRI, magnetic resonance imaging; T, Tesla